2020
DOI: 10.1016/j.immuni.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Reticular Fibroblasts Expressing the Transcription Factor WT1 Define a Stromal Niche that Maintains and Replenishes Splenic Red Pulp Macrophages

Abstract: Highlights d RPMs are embedded in a meshwork of WT1, CSF1expressing RP fibroblasts d RP fibroblasts represent a unique subset of splenic stromal cells d RP-fibroblast-derived CSF1 controls homeostasis of RPMs d RP fibroblasts participate to the recruitment of monocytes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 101 publications
(115 reference statements)
7
93
1
1
Order By: Relevance
“…Cells within the Coch+ cluster corresponded to red pulp fibroblasts and alveolar fibroblasts, as determined by higher expression of Wt1, Csf1 (red pulp fibroblasts) and Npnt and Ces1d (alveolar fibroblasts) 34,3941 relative to universal fibroblasts. This is consistent with observations showing that Wt1 -expressing red pulp fibroblasts maintain red pulp macrophage homeostasis via provision of Csf1 39 , though it is unclear if these mechanisms apply in the lung. The Cxcl12+ cluster was a mix of Lepr + mesenchymal stromal cells which express Lepr and Adipoq and mesenchymal-derived Emb+, Sp7+ osteolineage cells 21,4244 , two cell types that are known to regulate hematopoietic niches in the bone microenvironment.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Cells within the Coch+ cluster corresponded to red pulp fibroblasts and alveolar fibroblasts, as determined by higher expression of Wt1, Csf1 (red pulp fibroblasts) and Npnt and Ces1d (alveolar fibroblasts) 34,3941 relative to universal fibroblasts. This is consistent with observations showing that Wt1 -expressing red pulp fibroblasts maintain red pulp macrophage homeostasis via provision of Csf1 39 , though it is unclear if these mechanisms apply in the lung. The Cxcl12+ cluster was a mix of Lepr + mesenchymal stromal cells which express Lepr and Adipoq and mesenchymal-derived Emb+, Sp7+ osteolineage cells 21,4244 , two cell types that are known to regulate hematopoietic niches in the bone microenvironment.…”
Section: Resultsmentioning
confidence: 98%
“…This approach suggested that the Ccl19+ cluster was composed of fibroblastic reticular cells, which regulate immune cell localization and function in secondary lymphoid organs 3 . Cells within the Coch+ cluster corresponded to red pulp fibroblasts and alveolar fibroblasts, as determined by higher expression of Wt1, Csf1 (red pulp fibroblasts) and Npnt and Ces1d (alveolar fibroblasts) 34,[39][40][41] relative to universal fibroblasts. This is consistent with observations showing that Wt1-expressing red pulp fibroblasts maintain red pulp macrophage homeostasis via provision of Csf1 39 , though it is unclear if these mechanisms apply in the lung.…”
Section: Cross-tissue Transcriptional Panorama Of Fibroblasts In Steamentioning
confidence: 98%
“…As discussed by van Esbroeck et al (65), this could be the case of Abhd6 DAG lipase activity. As another example, conditional deletion of colony stimulating factor 1 (Csf1) selectively in spleen red pulp fibroblasts dramatically altered red pulp macrophage content without any change in the level of circulating Csf1 (66). The same reason might also explain the small but nonsignificant increase of brain LPI observed in KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that engulfment of dying erythrocytes, which both populations perform millions of times a day (24,44), provides the key defining source of heme. Alternatively, splenic red pulp macrophages are seeded in a WT1+ stromal network similar to that observed in Kupffer cells (45), which may synthesize and release heme that is subsequently imported via the heme transporter HCP1 (SLC46A1) (46,47).…”
Section: Metabolic Regulation Of Tissue-resident Macrophage Identitymentioning
confidence: 99%
“…Conversely, rapamycin-insensitive mTORC2 acts as a negative regulator of GATA6, and its suppression is required for peritoneal TRM differentiation (52). Given that WT1+ stromal cells are a major constituent in two unrelated tissue environments (45,50), it seems reasonable to conjecture that WT1+ stromal cells are a major non-cell-autonomous regulator of TRM metabolism. In support of this hypothesis, two independent studies observed that the liver also features WT1+ hepatic stellate cells that appear to be important regulators of liver fibrosis and scarring (53,54).…”
Section: Metabolic Regulation Of Tissue-resident Macrophage Identitymentioning
confidence: 99%